Peningkatan Kreatifitas Siswa Melalui Kegiatan Lomba Mewarnai dan Sosialisasi dengan Film Bullying di SD Negeri Sindon 1 - Indriastiningsih, Erna; Afif Mar'ah Iftinan Nur Firdaus; Nanding Arief Ekhsandy; Agung Widiyanto Fajar Sutrisno; Bekti Nugrahadi; Annisa Indah Mutiasari (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
Real Work Lecture (KKN) activities are carried out outside campus with the aim of increasing the relevance of higher education to development and society's need for science, technology and art to carry out development which is increasing, where students' perceptions of the relevance of the curriculum studied on campus with the reality of development in society. Where the aim of the Real Work Lecture is to guide and direct students in increasing creativity through coloring competition activities and socialization through bullying films at Sindon 1 State Elementary School. This research uses a qualitative type of research in this activity, coloring picture competitions with plant and animal themes for grades 1-3 and screening of films about bullying for grades 4-6. The implementation method approach uses two types, namely the student education approach with the student companion model, while the data collection process is carried out using participant observation techniques and literature study using the Miles and Huberman analysis model but supplemented with data triangulation tests. The results of the activity showed that students' creativity with the picture coloring competition and socialization through showing films about bullying went according to expectations, as evidenced by the participation of all students in grades 1-3 and grades 4-6. The level of enthusiasm is high due to their participation in delivering material and practical activities and students are able to understand the theory and knowledge related to the process of coloring pictures and there is awareness among students to live in harmony, respect and help each other and not carry out bullying which is detrimental to friends.